Combined observational and experimental data provide limited support for facilitation in lichens. Issue 2 (29th June 2015) - Svensson, Måns; Caruso, Alexandro; Yahr, Rebecca; Ellis, Christopher; Thor, Göran; Snäll, Tord
Abstract : It is increasingly recognized that facilitative interactions can shape communities. One of the mechanisms through which facilitation may operate is when one species facilitates the colonization of another through the exchange of shared symbionts. Lichens are symbiotic associations composed of a mycobiont (lichenised‐fungus) and one or two photobionts (algae or cyanobacteria). Different lichen species may have overlapping specificity for photobionts, creating the possibility that facilitation drives lichen community assembly. To investigate whether facilitation occurs in lichens, we combined an observational study (a) with a manipulative field experiment (b). For (a), we quantified the effect of local patch conditions, facilitation and the size of the surrounding metapopulation on colonizations of an epixylic lichen species ( Cladonia botrytes ) in an area of managed boreal forest. This was done by twice surveying lichens on 293 stumps, located in stands of three age classes. For (b), we treated unoccupied surfaces of 56 cut stumps with algal mixtures of an Asterochloris photobiont and recorded C. botrytes colonizations over three years. In (a), colonization rates of C. botrytes increased with increasing abundance of other lichen species with specificity for Asterochloris photobionts, consistent with an effect of facilitation. However, in the field experiment (b), colonizations of the focal species did not provide support for facilitation. We conclude that our study provides limited support for facilitation in green‐algal lichens, underscoring the importance of combining observational studies with experiments when studying species interactions.